The Strategy of Whisper Chain Game in Teaching Listening Skill to Students of Al-Uswah Islamic Boarding School Tahfidz Al-Quran at Pangarangan Sumenep - Annisa Mamluatul Barokah; Luthfatul Qibtiyah (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2024)
The aims of this research are to find out the implementation process of the whisper chain game used and the supporting and inhibiting factors in the process of teaching listening skill to students of Al-Uswah Islamic Boarding School Tahfidz Alquran at Pangarangan Sumenep. This research is a qualitative research with a descriptive approach. Data collection techniques were used in this research through interview and observation. The informants of this research are the teacher's listening skill and the directorate of student affairs and students. The data analysis used is the Saldana, Miles, and Huberman model which consists of data condensation, data presentation, and conclusions. The results of this research indicate that the whisper chain game used by the school has several steps, namely: The teacher says hello to all students to start teaching, then the teacher gives directions and explains a little about the introduction of the listening skill, and the teacher orders several students to divide their tasks in the teaching process, then the teaching activities are carried out by dividing groups to implement the game, then the teacher will provide explanations when misunderstandings appear, or add deficiencies that were not conveyed and will correct if there are errors conveyed by the students' affairs, and after the teaching process is completed, the teacher evaluates the teaching results that have been implemented and concludes the lesson with a greeting. The inhibiting factors that hinder students during the process of teaching the listening skill at Al-Uswah Islamic Boarding School Tahfidz Alquran at Pangarangan Sumenep are as follows: Feeling lazy in studying, lack of desire to learn, lack of concentration during the teaching process. Supporting factors that support the process of teaching listening skills, including: active learning strategy, student activity, group cohesion, flexible role of teachers, and evaluation.Keywords: Strategy, whisper chain game, listening skill